Solution‐Processed Fullerene‐Based Organic Schottky Junction Devices for Large‐Open‐Circuit‐Voltage Organic Solar Cells. (2nd November 2012) - Yang, Bin; Guo, Fawen; Yuan, Yongbo; Xiao, Zhengguo; Lu, Yunzhang; Dong, Qingfeng; Huang, Jinsong
<x xml:space="preserve">Abstract</x> A solution‐processed fullerene‐based organic Schottky junction photovoltaic device is fabricated to produce a large open circuit voltage, 0.85–0.95 V, which is higher than that of most organic bulk‐heterojunction devices. A power conversion efficiency of 5% is achieved in fullerene‐derivative [6, 6]‐phenyl‐C71‐butyric acid methylester‐based Schottky junction devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>